2003
DOI: 10.1017/s0144686x02008954
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the caring capacity of informal networks of frail seniors: a case for care networks

Abstract: Population ageing and constraints on public sector spending for older people with long-term health problems have led policy makers to turn to the social networks of older people, or the ‘informal sector’, as a source of long-term care. An important question arising from this policy shift is whether these social networks have the resources to sustain the high levels of care that can be required by older people with chronic health problems. In the face of both dire warnings about the imminent demise of the infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 34 publications
1
93
0
Order By: Relevance
“…Glendinning, 1992;Daly and Lewis, 2000;Williams, 2001;Fine, 2007;Ungerson and Yeandle, 2007;Williams, 2010;Barnes, 2012); gerontologists (e.g. Twigg and Atkin, 1994;Phillips et al, 2002;Keating et al, 2003;Walker, 2005a;Scharf, 2010); sociologists (e.g. Waerness, 1984;Phillipson, 1997;Daly, 2002;Peng, 2002;Anttonen and Sipila, 2003;Saraceno, 2008) and health academics (e.g.…”
Section: Care and Caring: Themes And Focusmentioning
confidence: 99%
“…Glendinning, 1992;Daly and Lewis, 2000;Williams, 2001;Fine, 2007;Ungerson and Yeandle, 2007;Williams, 2010;Barnes, 2012); gerontologists (e.g. Twigg and Atkin, 1994;Phillips et al, 2002;Keating et al, 2003;Walker, 2005a;Scharf, 2010); sociologists (e.g. Waerness, 1984;Phillipson, 1997;Daly, 2002;Peng, 2002;Anttonen and Sipila, 2003;Saraceno, 2008) and health academics (e.g.…”
Section: Care and Caring: Themes And Focusmentioning
confidence: 99%
“…This situation has influenced the types of interpersonal and trans-human care relations of those ageing in place that have come to the attention of researchers. The rationalities of neo-liberalism have evolved such that many community dwelling individuals must care for themselves or seek their own care-giving resources and support as required with informal, familial based modes of assistance the primary means of caregiving and with supplementation by formal health and social care services (Keating et al, 2003). Lawson(2007) cautions against this approach and advocates that an appropriate equilibrium between the ideals of care as personalised practice and as politics must be reached.…”
Section: Nursing Relationship Is the Core Of Ageing In Placementioning
confidence: 99%
“…Barrett et al(2012) found, for instance, that"receivers of care were less concerned with the performance of the practical, physical care tasks than with the personal connection implicit in the care relationship" . Relatedly, Keating et al(2003) have researched the capacity of personal social networks to evolve into support networks and found that the number of"tie ins"and size of, an older person' s social network is not necessarily a predictor of the capacity to'care' . Within a person' s social network there will be a potentially very small personal network of people whose ties to the individual are closer than others (Keating et al, 2003).…”
Section: The Effect Of Interpersonal Relationships On Health Care Of mentioning
confidence: 99%
See 1 more Smart Citation
“…She reinforces the centrality of collective responsibility in bold as a counter to the current dominant political discourses that refer to individual accountability and duty for ensuring sustainability, health and agency. At the same time, we are mindful of current trends for policy makers to turn to 'communities' and the 'informal sector' to provide support, caring, social services and resources as the welfare state shrinks (Jamrozik 2009;Keating et al 2003;Ife 2002).…”
Section: Connecting Craft Group Activity With Community Development Pmentioning
confidence: 99%